People's interest in brain health testing: findings from an international, online cross-sectional survey - Carver, RB; Fredheim, NAG; Mowinckel, AM; Ebmeier, KP; Friedman, BB; Rosness, TA; Drevon, CA; Suri, S; Baaré, WFC; Zsoldos, E; Solé-Padullés, C; Bartrés-Faz, D; et al. (Frontiers Media, 2022)
Brain health entails mental wellbeing and cognitive health in the absence of brain disorders. The past decade has seen an explosion of tests, cognitive and biological, to predict various brain conditions, such as Alzheimer's Disease. In line with these current developments, we investigated people's willingness and reasons to—or not to—take a hypothetical brain health test to learn about risk of developing a brain disease, in a cross-sectional multilanguage online survey. The survey was part of the Global Brain Health Survey, open to the public from 4th June 2019 to 31st August 2020. Respondents were largely recruited via European brain councils and research organizations. 27,590 people responded aged 18 years or older and were predominantly women (71%), middle-aged or older (>40 years; 83%), and highly educated (69%). Responses were analyzed to explore the relationship between demographic variables and responses.